The Relationship Between Body Mass Index and Hamstring Muscle Flexibility of Japanan Club Taekwondo Athletes - Selly Omega Dila Teju; Gabriel Wanda Sinawang (PROMOTOR, 2023)
An essensial for taekwondo athletes’ performance is flexibility. A nice example of hamstring flexibility is the action of kicking over the head. However, the body’s fat content can restrict this flexibility by limiting the joints’ range of motion. Taekwondo practitioners therefore need to demonstrate their flexibility and body mass index well. This study sought to ascertain how taekwondo athletes’ body mass index and hamstring muscle flexibility related to each other. This study design employs a correlation design in non-experimental quantitave research. The Active Knee Extension Test is used to measure hamstring flexibility, and weight scales and meters are used to calculate body mass index. Result: The Rank Spearman correlation test returned a value of p= 0,869 (p>0,05), indicating that there is no meaningful relationship between hamstring flexibility and body mass index in taekwondo practitioners. Conclusion : Among taekwondo athletes, there is no discernible correlation between hamstring flexibility and body mass index.